Design – key element of creative industries in Romania and its role in Romanian export - LIANU, Costin; GUDEI, Simona Corina (Annals of Spiru Haret University. Economic Series, 2012)
Creative industries are now considered a solution for sustainable development. EU 2020 strategy is considering these industries crucial for the future industrial policy of EU. In recent years, while some European countries or even regions and cities, such as the UK, Scandinavian countries cities like Barcelona, Tallinn, Copenhagen or Amsterdam to name a few, have been good at tapping into the extraordinary potential of the cultural and creative sectors as a way to promote socioeconomic development and progressively developed ad hoc strategies, others are only just starting. Present papers is aiming at evaluating potential of these industries in Romania, with focus on design, and their possible place in the future export development of the country. Where strategies have emerged, they tend to focus on the strengthening of these sectors and not yet on stimulating partnerships and spill-overs with other sectors.